Physicochemical, biological and β-haematin inhibiting activity of pyrido-dibemequines, pyrido[1,2-α]benzimidazoles and their derivatives - Okombo, Ojwang' John (Department of Chemistry, 2018)
There is an urgent need for new antimalarials following the emergence of Plasmodium falciparum strains with reduced sensitivity to the currently used artemisinin combination therapies. Classical aminoquinoline-based drugs inhibit the formation of haemozoin (HZ) thereby causing parasite death from the cellular accumulation of toxic 'free' haem. Coincidentally, this immutable pathway also exists in Schistosoma mansoni, and presents a vulnerable target for drug design in these haematophagus organisms. Therefore, it would be of interest to explore novel scaffolds that can inhibit HZ formation as well as exploit the merits of established drugs via structural modifications that would harness their pharmacological and pharmacokinetic advantages while circumventing their therapeutic shortcomings. This project investigated the physicochemical, biological and mechanistic profiles of pyrido-dibemequine (pDBQ) and pyrido[1,2-α]benzimidazole (PBI) derivatives whose structural motifs were informed by previously synthesised prototype molecules. Specifically, the aqueous solubility, membrane permeability, lipophilicity, metabolic stability and potential for cardiotoxicity of seven pDBQs, their metabolites and ten PBIs were tested through computational and experimental methods. In addition, their antiplasmodial and antischistosomal activities were determined and correlated with their respective physicochemical properties. As regards mechanistic evaluation, their ability to inhibit formation of abiotic HZ, β-haematin (βH), was assessed and intracellular inhibition of HZ formation probed. The pDBQs constitute reversed chloroquines with a 4-aminoquinoline nucleus hybridised to a dibenzylmethylamine side group that serves as a chemosensitising moiety. The pDBQ derivatives showed moderate to high solubility (52 - 197 μM) and permeability (LogPₐₚₚ: -4.6 - -3.6) at pH 6.5. Their lipophilicity, indexed by cLogP, ranged between 3.7 and 5.6 while the mean LogD at both cytosolic (7.4) and vacuolar (5.0) pH was 3.15 and 0.93, respectively. The compounds also showed low-nanomolar range antiplasmodial activity against both chloroquine (CQ)-sensitive (CQS) and resistant (CQR) strains (IC₅₀ range CQS: 14.4 - 126.6 nM, CQRᴰᵈ²: 44.5 - 162 nM and CQR⁷ᴳ⁸: 69.6 - 307.1 nM), with no discernible cross-resistance with CQ and the antiplasmodial activity directly correlated with lipophilicity. Mechanistically, all the pDBQs inhibited βH formation (IC₅₀: 13 - 25 μM) and haem-pyridine fractionation profiles revealed they produced a CQ-like dose-dependent increase in toxic 'free' haem with corresponding decrease in HZ levels. Predicted human-Ether-a-Go-Go-Related Gene (hERG) channel inhibition pIC₅₀ ranged between 6.2 and 6.6, and correlated strongly with the cLogP and molecular weight. The derivatives were also highly susceptibility to microsomal metabolism, with N-dealkylation identified as the main biotransformation route. The pDBQ metabolites exhibited solubility and membrane permeability profiles similar to the parent compounds at pH 6.5, albeit with reduced lipophilicity (cLogP range: 2.3 - 3.5). Their βH inhibition activity (IC₅₀: 15 - 24 μM) was also comparable to the parent compounds as were the haem-pyridine fractionation profiles. However, they showed greater antiplasmodial activity, with 4/7 derivatives exhibiting IC₅₀ < 80 nM against PƒDd2 (CQR strain). The metabolites had reduced hERG channel inhibition potential (pIC₅₀: 5.0 - 5.7) and significantly improved metabolic stability upon incubation with mouse and human liver microsomes. The PBIs comprise molecules with structural likeness to CQ, including a planar heterocyclic moiety and a basic amine side group. PBI analogues showed low to moderate solubility (<5 - 80 μM) and were moderately lipophilic (mean LogD7.4: 3.04). Although most of the derivatives were stable in liver microsomes, their predicted hERG channel inhibition potential was higher (pIC₅₀: 6.11 - 7.50), presumably due to their high molecular weights. All but one derivative had submicromolar activity against CQS and CQR strains, with analogues bearing halo-substituents on the left of the PBI core showing the best antiplasmodial activity (mean IC₅₀: CQS = 26.7 nM and CQR = 30.0 nM), highest selectivity (188 - 341) as well as complete cures in P. berghei-infected mice. The PBIs also inhibited βH formation (IC₅₀: 6.8 - 120 μM) but did not all display intracellular inhibition of HZ formation. All derivatives were active against juvenile (mean IC₅₀: 1.97 μM) and adult (mean IC₅₀: 4.38 μM) schistosomes, with the 3, 4-dichloro-substituted analogue exhibiting 48% reduction of worm burden in vivo. In summary, the pDBQs evaluated in this project constitute potent antiplasmodial inhibitors of HZ formation but whose activity is compromised by metabolic and hERG liability while their metabolites seem to possess improved biological and physicochemical features. The observed activity of the PBIs against P. falciparum and S. mansoni complements the already-established broad antimicrobial potency of this chemotype.